Factors Associated with Substance Use among Nurses and Midwives in Referral Hospitals in Botswana - Gaonyadiwe Lubinda; Onalenna Tsima; Mosidi Mokotedi (Africa Journal of Nursing and Midwifery, 2026)
Substance use among nurses and midwives is escalating globally. Nurses and midwives face numerous workplace challenges and resort to substance use to cope. The specific factors associated with substance use in this population group remain underexplored. The purpose of this study was to explore factors associated with substance use among nurses and midwives in referral hospitals. A qualitative, descriptive research design was employed. Based on saturation, a semi-structured interview guide was used to collect data from purposively selected 38 nurses and midwives working in three referral hospitals. Researchers collected data through interviews, audio-recordings, and field notes. Thematic data analysis was employed using the six steps of the Braun and Clarke process. Nurses and midwives perceive numerous factors as contributing to substance use. Three major themes related to work, psychosocial, and economic factors emerged. Psychological support, recreational activities, and rehabilitation were suggested as ways to assist in curbing substance use behaviours. The results may inform policy development, guidelines, and standard operating procedures to guide nursing practice, protect patient safety, and promote quality care. They will also inform curriculum development to emphasise adaptability and resilience during periods of work stress and hardship. Prevention and rehabilitation interventions to support nurses and midwives are critical in ensuring the safety of patients, nurses, and midwives.